Family-based adverse childhood experiences as a determinant of learner drug abuse in Soweto high schools: implications for early intervention - Mnyamana, Nzukiso Theophillus (University of the Witwatersrand, Johannesburg, 2024)
Drug abuse is the excessive, maladaptive, or addicted use of drugs for purposes other than those prescribed by a doctor, even if this usage may lead to social, psychological, and physical issues. Learners who abuse drugs have a higher risk of developing mental health issues, such as depression, conduct issues, personality disorders, suicidal ideation, attempted suicide, and suicide, than learners who do not. Resounding evidence suggests that despite all the restrictions put in place by schools regarding substance abuse, it is nevertheless pervasive on school grounds in the Soweto region. It has been reported that alcohol, tobacco, and hallucinogens are the most often used drugs and substances among teenagers in Soweto. Additionally, it has been reported that drug misuse among learners in secondary schools in the Soweto district of South Africa is on the rise. Despite previous research having been done to address drug abuse among learners, there is still very scanty research on the effect of family based adverse childhood experiences. The main goal of this study was to examine the effect and correlation of family based Adverse Childhood Experiences and the escalating learner drug abuse among learners in township High schools in Soweto. The study also looked at the kind of support that are available at home for learners who are involved in drug abuse and early home based intervention strategies that could be adopted to assist learners who abuse drugs. Finally, the study sought to develop a structural equation modelling that can explain the relationship between biographical factors, familial psychological and familial social factors and learner drug abuse. Within the mixed methods research paradigm, concurrent triangulation research design was adopted. Thus, by adopting a mixed methods research methodology, target population comprised 80 High School learners at the selected four Soweto High Schools in Gauteng Central District. For the quantitative phase, 80 High School learners from four Soweto High Schools were obtained using a census sampling technique. A sample size of 16 High School learners was chosen for interviews during the qualitative phase of the study using the purposive sampling method. Parental Behavioral Control Scale, Parent-Child Attachment Patterns Scale, Emotional Breakdown Scale, Induced Psychological Disorders Scale, Parent–Adolescent Relationship Scale, Sibling Influence Scale, Parental Influence Scale and Home Based Support scale were used to collect quantitative vii data from learners. Semi-structured interviews with learners were conducted to gather information for the qualitative phase. The Keyser Meyer Oklin test was used to guarantee the validity of the questionnaires, and Cronbach's alpha was used to determine their reliability. Additionally, the trustworthiness of qualitative data was ensured. The findings of the study indicated that the biographical factors such as family type, family size, parental level of income, and parental level of education had a significant influence on learner drug abuse. Furthermore, familial psychological factors such as cognitive factors, behavioural factors, emotional factors, parental behavioral control, parent-child attachment patterns, emotional breakdown and induced psychological disorders also had a significant influence on drug abuse. Moreover, the study equally revealed familial social factors, such as parent related factors, sibling related factors, and finally, community related factors to have a significant effect on learner drug abuse. The findings also indicated that familial social factors and familial psychological factors were significant predicators of drug use among the learners. Overall, the results revealed that the variables investigated in this study are suitable for use in structural equation for escalating learner drug abuse. In conclusion, the family systems model is appropriate and fit for demonstrating the structural relationship between psychological, social factors and learner drug abuse among High School learners. From the findings aforemetioned, the study proposes a 6-stage intervention Model which could assist learners in High Schools as far as drug abuse is concerned. The study recommends that the school counsellors and management should perform psychological assessment on learners to identify those that are at risk of indulgence in drugs. The psychological assessment on learners to identify those with birth order that are at risk of indulgence in drugs would help them to evaluate their own cognitive, intellectual, and problem-solving abilities so as to counter psychological patterns susceptible to drug abuse. The study recommends that the school management should provide parents with the essential educational support and advice about familial social issues that may have a bearing on learner drug abuse
A research report submitted in fulfillment of the requirements for the Doctor of Philosophy, In the Faculty of Humanities, Wits School of Education, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Family-Based; Adverse Childhood Experiences; Escalating; Learner; Drug Abuse; Soweto; High Schools; Early Intervention; SDG-4: Quality education